A trajetória de uma geração política no Espírito Santo : da universidade ao poder : 1982 a 1992 - Martin, Margô Devos (2008)
The political generation formed from the University Student’s Movement gets to Vitória City Hall through a group of people who contributed to the reopening of the DCE (Student’s Central Directory) of the Federal University of Espírito Santo in the year of 1979 and identifies in the Governor Paulo Hartung its main leader. The establishment of this group, formed by men and women, occurred while in search of the democratization of the Brazilian Politics, mainly the one from Espírito Santo, using political parties as a basis to consolidate the full democracy. The political scenery found at the end of the Military Regime, following the party systems closure, worsened because of the decay of the developing politics and showed a low institutionalization of the party systems, which was even more deteriorated by the beginning of the New Republic. Another aspect that contributed to the parties’ decaying is the growth of the television as a powerful electoral force, minimizing the importance of the political parties’ events and leading the candidate to present himself directly to his audience. Considering the chosen time, it is clear how involved this generation was in all the significant moments of the political history in Espírito Santo, in a growing course, competing in elections and taking part in outstanding positions in the public administration consummating in Paulo Hartung’s election to Vitória City Hall in 1992. By means of testimonies of individuals who participated in this course and sources like newspapers and magazines from that time, this research was directed by the Oral History methodology. Among the many individuals who participated in this political process, some stand out with their own characteristics, as part of a gear that contributed to the establishment of the group, keeping their own peculiarities and functions in the political engineering of this group’s unity, which later on, in 2002, became the main political power in Espírito Santo with the election of Paulo Hartung as the governor of the state. The influence of the Italian Communism Beliefs, inspired by the texts of Antônio Gramsci, who developed the concept of “war of positions”, led the group to their projects’ course, the search for the consensus, the gathering of personnel and the networking creation, which shifted to the public power.